PELATIHAN PENYELENGGARAAN JENAZAH DI MASJID AL-MUTHMAINNAH JONDUL RAWANG - Ramadhanul Ikhsan; Martin Kustati; Gusmirawati Gusmirawati (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2023)
Training on handling corpses at the Al-Muthmainah Mosque in Jondul Rawang was held because of the lack of knowledge, skills and desire of teenagers and young people around the mosque to handle corpses. This condition can be seen when deaths occur around the mosque, where only the elderly members of the death congregation are able to carry out this task. Meanwhile, teenagers and youth do not have the knowledge and courage to take care of corpses because they lack understanding of the procedures. Seeing this phenomenon, administrators and religious leaders at the Al-Muthmainah Mosque in Jondul Rawang decided to hold training on handling corpses. The aim of this activity is to increase the knowledge, skills and desires of teenagers and young people around the mosque in caring for corpses. In this training, a participatory action research strategy was used with the explicit instruction method. The impact of this training can be seen in increasing knowledge, skills, and teenagers and young people around the Al-Muthmainah Mosque in Jondul Rawang being confident in carrying out the task of handling corpses. As a result, they are better prepared to implement the correct procedures when facing death around the al-Muthmainah mosque